Functionalization of recycled polymer and 3D printing into porous structures for selective recovery of copper from copper tailings - Ibebunjo, Kosisochi; El Ouardi, Youssef; Kwame Bediako, John; Iurchenkova, Anna; Repo, Eveliina (Chemical engineering science, 2024)
Selective copper recovery from copper tailings reduces environmental pollution caused by mining activities and provides a valuable source of copper. Furthermore, polymer waste accumulation and handling small functional materials like resins remains challenging. In this study, a 3D-printed adsorbent for selective copper recovery from copper tailings was designed by functionalizing recycled polymer with a chelating resin and 3D-printing using selective laser sintering technique. The 3D-printed adsorbent was characterized, and its adsorption performance examined under varying conditions. The adsorption kinetics and adsorption isotherm fitted well to the pseudo-second-order kinetics and Langmuir isotherm models, suggesting chemical and monolayer adsorption processes. FTIR indicated coordination as the possible adsorption mechanism. Thermodynamics revealed an endothermic process. The 3D-printed adsorbent demonstrated an excellent Cu(II) adsorption, high selectivity towards Cu(II), and reusability. This work offers a promising 3D-printed adsorbent for selective Cu(II) recovery, while also addressing polymer waste and particle handling issues.